Nature-Based Solutions for Urban Climate Change Adaptation and Wellbeing: Evidence and Opportunities From Kiribati, Samoa, and Vanuatu - Kiddle, Gabriel L.; Bakineti, Tokintekai; Latai-Niusulu, Anita; Missack, Willy; Pedersen Zari, Maibritt; Kiddle, Rebecca; Chanse, Victoria; Blaschke, Paul; Loubser, David (Frontiers in Environmental Science, 2021)
Climate change and urbanisation in combination put great pressure on terrestrial and ocean ecosystems, vital for subsistence and wellbeing in both rural and urban areas of Pacific islands. Adaptation is urgently required. Nature-based solutions (NbS) offer great potential, with the region increasingly implementing NbS and linked approaches like ecosystem-based adaptation in response. This paper utilises three Pacific island nation case-studies, Kiribati, Samoa and Vanuatu, to review current NbS approaches to adapt and mitigate the converging resilience challenges of climate change and urbanisation. We look at associated government policies, current NbS experience, and offer insights into opportunities for future work with focus on urban areas. These three Pacific island case-studies showcase their rich cultural and biological diversity and, importantly, the role of traditional ecological knowledge in shaping localised, place-based, NbS for climate change adaptation and enhanced wellbeing. But gaps in knowledge, policy, and practice remain. There is great potential for a nature-based urban design agenda positioned within an urban ecosystems framework linked closely to Indigenous understandings of wellbeing.